Takhrij Hadith the Importance of Silaturahmi in the Islamic World - Ghoni, Muhamad Ilman Maulana Nata Abdul; Busro, Busro (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about friendship. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is takhrij hadith within the scope of hadith science, while the material object is the hadith about friendship in the history of Bukhari no. 5527. The results and discussion of this study indicate that the quality of the hadith regarding friendship is assessed as maqbul ma'mul bih with hasan li ghairihi qualifications. This study concludes that the hadith narrated by Bukhari no. 5527 is relevant to be used as a motivation for increasing friendship in the Muslim community.